Media Sosial dan Pengaruhnya terhadap Pengetahuan Remaja tentang Dampak Kehamilan di Usia Remaja - Andi Basniati; Andi Sulastri; Mutmainna Kamaruddin; Sunarti Sunarti; Selviana Tawil (Journal of Telenursing (JOTING), 2026)
This study aims to determine the effect of using social media as a means of health education on changes in adolescents' knowledge levels regarding the impact of teenage pregnancy. The method used was a quantitative experimental study with a pre-test and post-test. The results of the t-test showed that social media influenced adolescents' knowledge regarding the impact of teenage pregnancy. There was a difference in knowledge before and after receiving health education in the form of social media and its influence on changes in adolescents' knowledge regarding the impact of teenage pregnancy, with a p-value (0.000) < 0.05 or a calculated Z-value (6.113) > Z-table (1.96). In conclusion, social media significantly influenced changes in adolescents' knowledge levels regarding the impact of teenage pregnancy, indicating that appropriate education through social media can be an effective strategy to increase their understanding.   Keywords: Education, Social Media, Knowledge, Adolescents